The Effect of Different Doses of Compost and Urea Fertilizer on the Growth of Pak Choi (Brassica rapa L.) - Merta, I Wayan; Raksun, Ahmad (Jurnal Pijar Mipa, 2025)
Pak Choi is a widely cultivated plant species in Indonesia. To grow optimally, Pak Choi requires a growing medium containing sufficient nutrients. To ensure adequate nutrient levels in the growing medium, fertilization is necessary. Research on the effect of compost and urea fertilizer applications on Pak Choi growth was conducted from March to June 2025. This study aims to analyze the vegetative growth of Pak Choi after being given compost and urea fertilizer treatments. In this study, a completely randomized design with 2 factors was used. The compost application was 0 kg, 0.8 kg, 1.6 kg, and 2,4 kg for 8 kg of soil in a polybag. The urea fertilizer treatment was 0 grams, 0.5 grams, 1 gram, and 1.5 grams for each plant. Each treatment combination was performed with three replications. The results showed that the compost treatment had a significant effect on the fresh weight, number of leaves, plant height, and leaf length of Pok choy. The application of urea fertilizer can increase the fresh weight, number of leaves, plant height, and leaf length of Pak Choi. The interaction between compost and urea fertilizer had no significant effect on fresh weight, leaf number, plant height, or leaf length. The optimal dose of compost was 1.2 kg. The 1.5-gram urea fertilizer treatment resulted in better growth than the other doses.